Analisis status Posyandu dan kepemilikan layanan kesehatan diwilayah Dinas Kesehatan Kabupaten Sukoharjo: Studi kasus tahun 2017-2021 - Ismiyatun Ismiyatun; Noor Alis Setiyadi (Journal of Health and Therapy, 2023)
This study examined the status of posyandu and described the ownership of health services in the working area of the Sukoharjo District Health Office during 2017–2021. This descriptive study used secondary data reported by 12 puskesmas to the Sukoharjo District Health Office, including posyandu data and health service ownership. Data were analyzed descriptively and presented in graphs. Sukoharjo Regency consists of 12 sub-districts, each served by one puskesmas. Sociodemographic data show that the population decreased from 899,550 people in 2017 to 891,923 people in 2018, a decline of approximately 0.9 percent. The analysis of posyandu status indicated fluctuating trends over the 2017–2021 period, with an increase in 2018 and a decrease in 2020 in the working areas of Bulu and Grogol puskesmas. In contrast, in the other 10 puskesmas, there was no increase in the number of posyandu throughout the study period.